IMPLEMENTASI SISTEM PIERCING THE CORPORATE VEIL PADA CHATTERLY V OMNICO SELAKU PERUSAHAAN INDUK DARI INTERFACE COMPUTER - Kartika Cahyaningtyas; Muh. Isra Bil Ali (JURNAL SUMBER HUKUM, 2024)
This study examines and analyzes the implementation of the piercing the corporate veil system in limited liability companies. This needs to be studied because there are still limited liability companies that implement it incorrectly. The method used is normative research with a statutory and case approach. The results are in the form of the implementation of piercing the corporate veil applied in a company experiencing unstable economic conditions caused by deviant behavior from the board of directors that is not beneficial for the company. This makes the implementation of the piercing the corporate veil system at Omnico based on the fact that Omnico is the majority shareholder in the Interface company and is actively involved in managing the business in Interface and there are concurrent positions on the board of directors or officers on the Omnico board and the board structure at Interface. The withdrawal of funds by the majority shareholder resulting in the subsidiary being unable to pay its obligations to employees is considered an act of diversion of funds by the majority shareholder. Omnico is also responsible for everything related to Interface. This is because Omnico has bought up to 80% of Interface's shares and is actively involved in managing the business. Keywords: Piercing the corporate veil, Unstable conditions, Board of Directors, Deviant behavior